Metabolic profiling study on potential toxicity in male mice treated with Dechlorane 602 using UHPLC-ESI-IT-TOF-MS. (March 2019) - Tao, Wuqun; Tian, Jijing; Xu, Tuan; Xu, Li; Xie, Heidi Qunhui; Zhou, Zhiguang; Guo, Zhiling; Fu, Hualing; Yin, Xuejiao; Chen, Yangsheng; Xu, Haiming; Zhang, Songyan; et al.
Abstract: Dechlorane 602 (Dec 602), a chlorinated flame retardant, has been widely detected in different environmental matrices and biota. However, toxicity data for Dec 602 seldom have been reported. A metabolomics study based on ultra-high performance liquid chromatography coupled with ion trap time-of-flight mass spectrometry was employed to study the urine and sera metabolic profiles of mice administered with Dec 602 (0, 0.001, 0.1, and 10 mg/kg body weight per day) for 7 days. A significant difference in metabolic profiling was observed between the Dec 602 treated group and the control group by multivariate analysis, which directly reflected the metabolic perturbations caused by Dec 602. The metabolomics analyses of urine from Dec 602-exposed animals exhibited an increase in the levels of thymidine and tryptophan as well as a decrease in the levels of tyrosine, 12, 13-dihydroxy-9Z-octadecenoic acid, 2-hydroxyhexadecanoic acid and cuminaldehyde. The metabolomics analyses of sera showed a decrease in the levels of kynurenic acid, daidzein, adenosine, xanthurenic acid and hypoxanthine from Dec 602-exposed animals. These findings indicated Dec 602 induced disturbance in phenylalanine, tyrosine and tryptophan biosynthesis, tryptophan metabolism, tyrosine metabolism, pyrimidine metabolism, purine metabolism, ubiquinone and other terpenoid-quinone biosynthesis; phenylalanine metabolism and aminoacyl-tRNA biosynthesis. Significant alterations of immune and neurotransmitter-related metabolites (tyrosine, tryptophan, kynurenic acid, and xanthurenic acid) suggest that the toxic effects of Dec 602 may contribute to its interactions with the immune and neuronal systems. This study demonstrated that the UHPLC-ESI-IT-TOF-MS-based metabolomic approach can obtain more specific insights into the potential toxic effects of Dec 602 at molecular level. Graphical abstract: Analysis of sera and urine metabolomics phenotypes toxicity of chlorinated flame retardant Dechlorane 602 in male mice using UHPLC-ESI-IT-TOF-MS coupled with pattern recognition methods. Image 1 Highlights: The immune and neurotransmitter-related metabolites were significantly affected. Dec 602 caused the metabolic perturbations. Metabolomics helps to understand how environmental chemicals affect the organisms. Abstract : Significant alterations of relative metabolites suggest that Dec 602 may contribute to its toxic interactions with the immune and neuronal systems.